Effect of dietary omega-3 fatty acid supplementation on frailty related phenotypes in older adults: a systematic review and meta-analysis protocol - Stocks, Joanne; Valdes, Ana M. (BMJ Publishing Group Ltd, 2018)
Introduction: The beneficial effect of dietary omega-3 supplementation in younger adults or older people with acute or chronic disease is established. Knowledge is now needed about the effect in medically stable older people. The objective of this study is to examine and assess the evidence for a role of dietary omega-3 polyunsaturated fatty acid (PUFA) supplementation in older adults on (1) muscle mass and muscle strength, (2) inflammatory biomarkers and (3) physical activity. Methods and analysis: A systematic review and data synthesis will be conducted of randomised controlled trials in older people not recruited for any given disease diagnosis. Placebo-controlled studies reporting interventions involving dietary supplementation of omega-3 PUFAs, eicosapentaenoic acid and docosahexaenoic acid will be included. Outcomes must include changes from baseline to last available follow up for one or more of the following: muscle mass, inflammatory biomarkers, physical activity, walking speed, weight change, hand grip strength or muscle strength. Once the search strategy has been carried out, two independent researchers will assess relevant papers for eligibility. Articles up until 31 December 2017 in any language will be included. We will provide a narrative synthesis of the findings from the included studies. Studies will be grouped for meta-analysis according to the outcome(s) provided. Where studies have used the same type of intervention, with the same outcome measure, we will pool the results using a random effects meta-analysis, with standardised mean differences for continuous outcomes and risk ratios for binary outcomes, and calculate 95% CI and two-sided p values for each outcome. Ethics and dissemination: No research ethics approval is required for this systematic review as no confidential patient data will be used. The results of this systematic review will be disseminated through publication in an open-access peer-reviewed journal and through conference presentations.